2013
DOI: 10.1080/01446193.2013.828845
|View full text |Cite
|
Sign up to set email alerts
|

Managerial competencies of female and male managers in the Swedish construction industry

Abstract: The construction industry is one of the most male dominated industries around the world, not only when it comes to workers, but also as regards managers. Only 5% of the managers in the Swedish construction industry are women. The managerial competencies of individuals working as managers in the Swedish construction industry are researched to get a clearer understanding of the situation, and to investigate if this lack of balance between male and female managers has to do with differences in managerial competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
(57 reference statements)
0
27
1
Order By: Relevance
“…Laura's account runs counter to the findings of Arditi et al (2013) which indicate that female managers in construction, at least in Sweden, tend to conform to quite a traditional set of female gender behaviours. Laura embraces gendered strategies that are complex, not always distinctly masculine or feminine but often about different management styles.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Laura's account runs counter to the findings of Arditi et al (2013) which indicate that female managers in construction, at least in Sweden, tend to conform to quite a traditional set of female gender behaviours. Laura embraces gendered strategies that are complex, not always distinctly masculine or feminine but often about different management styles.…”
Section: Discussioncontrasting
confidence: 63%
“…For example, Arditi et al (2013) conclude that "female managers are as competent as male managers…" Language here re-affirms the doubt about women's place and position on a construction site instead of developing an argument for or a perception of gender-neutral management in construction. This trend is not unique to construction: "managerial discourses construct management as a task that requires the application of expertise and rational analysis to provide control over organisational activity and ultimately the realisation of organisational goals" (Hay, 2014: 510).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Powell (1990) concurred with Donnell and Hall and concluded that whatever differences that are reported between women and men managers are based on perception and stereotype. In their own study, Arditi, Gluch and Holmdahl (2013) found differences in the competencies of men and women, but also reported many similarities. These differences reflect the historical perceptions about men and women leaders and managers (Tomal & Jones, 2015;Dobbins & Platz, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Competencies generally entail the ability to apply acquired knowledge and other capabilities that are necessary for the efficient performance and achievement of predetermined organisational goals (Gruban, 2003). Thus, the type of managerial competency required in a male dominated industries, for example, mining, manufacturing and construction is not different from the one demonstrated in a seemingly female dominated industries, for example, nursing, healthcare, catering and hospitality (Dainty, Cheng & Moore, 2004;Arditi, Gluch & Holmdahl, 2013;Dreyfus, 2008;Barber & Tietje, 2004). This argument is indeed consistent with the definition of managerial competency which is a set of knowledge, skills, abilities and behaviours that enables effective performance and achievement of set organisational outcomes (Hellriegel, Jackson, Slocum, Staude, Amos, Klopper, Louw & Oosthuizen, 2004;Campion, et.…”
Section: Discussionmentioning
confidence: 96%